Quantification of Free Circulating DNA and Differential Methylation Profiling of Selected Genes as Novel Non-Invasive Biomarkers for Endometriosis Diagnosis - Moncef Benkhalifa; Pierre Alain Menoud; David Piquemal; Jack Y. Hazout; Sami Mahjoub; Mohammed Zarquaoui; Noureddine Louanjli; Rosalie Cabry; Andre Hazout (Biomolecules)
Endometriosis is a chronic, estrogen-dependent disorder associated with the presence of endometrial cells mainly in the pelvic cavity, causing systemic immune inflammation, infertility, epigenetic dysregulation of differential DNA methylation, coelomic metaplasia, and pain. It affects approximately 10–12% of women. Despite decades of research, full pathophysiology, a diagnostic roadmap, and clinical management strategies for endometriosis are not yet fully elucidated. Cell-free DNA (Cf-DNA) in the peripheral blood of diseased and healthy individuals was discovered in the 1950s. Quantifying peripheral Cf-DNA and the specific differential methylation of a group of genes have been proposed as potential non-invasive diagnostic biomarkers for somatic and constitutional genetics and for various other pathological disorders. In this study, we investigated the Cf-DNA levels of 78 young women, 38 of whom had endometriosis confirmed via laparoscopy and 40 of whom were healthy. We found a significant difference between the two groups when Cf-DNA was quantified, with 3.9 times more Cf-DNA in the serum of women with endometriosis. We also identified nine target genes potentially involved in the pathogenesis of endometriosis, with a different methylation profile between the two groups. Our data suggest that the combination of cell-free DNA quantification and the assessment of the epigenetic signature of differential methylation of nine genes can be proposed as a non-invasive predictive and diagnostic test for endometriosis.